International Handbook of Inter-religious Education - Engebretson, Kath.; Souza, Marian; Durka, Gloria; Gearon, Liam.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This Handbook has the potential to redress the distortion of information about particular religions, to add to understanding about what religions have in common, and to suggest how they can work together for justice and peace. In the present day there is a vital resurgence of interest in religions, with new movements emerging from long established religious traditions. There is also, around the world, a growing sense of the need to preserve indigenous religions, even when these have accommodated to imported traditions. The Handbook gives a voice to this resurgence of interest, and addresses inter-religious education from a range of religious viewpoints and contexts. The publication is very timely especially in light of the need for religions of the world to together contemplate and actively promote human rights, social justice and peace, for religions have a specific mandate for this.
Section one: The philosophical and theoretical aspects of inter-religious education -- Section two: Religious education for inter-religious engagement -- Section three: Inter-religious education for social justice and peace -- Section four: Inter-religious education for citizenship and human rights -- Name Index -- Subject Index.
Keywords: Education; Philosophy; Early childhood education; Education -- Philosophy; Religion (General).; Education; Sociology of Education; Educational Philosophy; Religious Studies; Childhood Education; Teaching and Teacher Education; Philosophy of Religion